First Capture of a Jaguar Using a Minimally Invasive Capture System for GPS Tracking in an Isolated Patch of Atlantic Forest in Southern Brazil - Francisco Palomares; Tarcízio Antônio Rego de Paula; Ana Carolina Srbek-Araujo (Animals, 2023)
This study presents the first successful capture using GPS tagging of a jaguar (Panthera onca) using a minimally invasive capture system (MICS). We used snare-foot traps and a MICS during two capture campaigns in a fragment of Atlantic Forest in southeastern Brazil. The specimen disarmed snares on different occasions, and capture was only possible with the MICS. The captured jaguar, an estimated 16-year-old adult male, was monitored using a GPS Vertex Plus Iridium collar with an optimal performance of 86% in expected locations. The jaguar’s home range (659 km2 by MPC and 174 km2 by 95%K) was within the observed range for the species and the animal was primarily maintained in protected areas. The habitat types most frequently used were native grassland (27.2% of 4798 fixes), marsh (24.8%), and dense lowland forest (24.7%). The use of a MICS for trapping jaguars is a promising technique that shows advantages in terms of efficiency, selectivity, portability, reduced potential risk of injury to animals or trappers, and animal stress compared to other capture methods used for the species.